Parker Solar Probe Observations of Compound Reconnection Exhaust Boundaries and Mirror-mode Structures in the near-Sun Heliospheric Current Sheet - Sun,W; Phan,T; Huang,J; Liu,YH; Slavin,JA; Romeo,O; Liu,M; Angelopoulos,V; Rahmati,A; Larson,D; Walia,N; Bale,S; et al. (Astrophysical Journal Letters, 2026)
Magnetic reconnection is a fundamental physical process that can drive rapid conversion of magnetic energy into plasma bulk flows, thermal heating, and particle acceleration in space and astrophysical plasmas. Classical reconnection theory predicts that the Alfvénic reconnection exhausts are bounded by pairs of slow-mode shocks. However, identifying and characterizing these shocks through in situ spacecraft observations remains a challenge. Here, we report Parker Solar Probe observations of a reconnection exhaust embedded in the heliospheric current sheet at a heliocentric distance of 12.2 (Formula presented) R. The reconnection exhaust is bounded on both boundaries by compound magnetic structures rather than a pair of pure slow shocks. Each boundary consists of a rapidly evolving, steep, inner slow shock, whose Mach numbers and shock-normal angles change significantly within several minutes, and an outer, gradual compound structure that comprises a slow shock and a rotational discontinuity. These slow shocks are quasi-perpendicular and are accompanied by enhanced proton perpendicular heating. Deep within the reconnection exhaust, high perpendicular temperature together with large plasma (Formula presented) β trigger mirror instability and generate mirror-mode structures. These observations provide new insights into the structure of reconnection exhaust boundaries and their role in energy conversion in the near-Sun plasma.